Epidemiology and healthcare burden of non-fatal maxillofacial injuries in Bangladesh: Evidence from Bangladesh Health and Injury Survey (BHIS), 2016 - Ruksana Sharmin Swarna; Mariam Zamila; Imteaz Mahmud; Israt Jahan Bushra; Monjur Rahman; Salim Mahmud Chowdhury; Mohammad Delwer Hossain Hawlader; Saidur Rahman Mashreky (PLoS ONE, 2026)
Background Maxillofacial injuries cause significant morbidity and contribute greatly to the global healthcare burden, yet epidemiological estimates from Bangladesh are lacking. This is the first population-level study to provide nationally representative estimates of the epidemiology, healthcare burden, and economic impact of such injuries in Bangladesh. Methods A secondary analysis was conducted using data from the Bangladesh Health and Injury Survey 2016, a national cross-sectional survey that utilised multistage cluster sampling to collect data from 292,217 individuals across all age groups with a six-month recall period. Annualised incidence rates (IRs) and incidence rate ratios (IRRs), with 95% confidence intervals (CIs), were estimated and stratified by sociodemographic, injury, and healthcare-related characteristics. Results The annual IR of non-fatal maxillofacial injuries was 793 (95% CI 760.3–824.8) per 100,000 population in 2016. Males (IR 989.1 per 100,000; 95% CI 938.1–1040.2), children aged 0–4 years (IR 1577.9 per 100,000; 95% CI 1414.9–1740.9), urban residents (IR 826.1 per 100,000; 95% CI 748.1–904.2), and auto-rickshaw/bus/truck drivers (IR 1632.7 per 100,000; 95% CI 1205.0–2060.3) experienced higher rates. Falls and road traffic accidents accounted for most cases, and 56.9% of injured individuals sustained concomitant injuries. Moreover, 47.4% of the injured did not receive any treatment, while 15.1% required hospital admission. The mean inpatient out-of-pocket (OOP) expenditure was USD 470.5 [standard deviation (SD) 1497.1]. Extrapolating the BHIS 2016 estimates to the 2026 national population projected an increase in non-fatal maxillofacial injury cases from 1.27 to 1.41 million. Conclusion A high incidence rate, a substantial treatment gap, and significant OOP costs underscore critical gaps in maxillofacial injury care in Bangladesh. Alongside reinforcing the country’s infrastructure, we call for targeted policy reforms to strengthen injury prevention, treatment, rehabilitation, and financial protection.